Activation of Symbiosis Signaling by Arbuscular Mycorrhizal Fungi in Legumes and Rice. Issue 3 (27th February 2015) - Sun, Jongho; Miller, J. Benjamin; Granqvist, Emma; Wiley-Kalil, Audrey; Gobbato, Enrico; Maillet, Fabienne; Cottaz, Sylvain; Samain, Eric; Venkateshwaran, Muthusubramanian; Fort, Sébastien; Morris, Richard J.; Ané, Jean-Michel; et al.
Abstract : Arbuscular mycorrhizal fungi produce a variety of signaling molecules that are shown to promote symbiosis signaling in a range of plant species. Abstract: Establishment of arbuscular mycorrhizal interactions involves plant recognition of diffusible signals from the fungus, including lipochitooligosaccharides (LCOs ) and chitooligosaccharides (COs ). Nitrogen-fixing rhizobial bacteria that associate with leguminous plants also signal to their hosts via LCOs, the so-called Nod factors. Here, we have assessed the induction of symbiotic signaling by the arbuscular mycorrhizal (Myc) fungal-produced LCOs and COs in legumes and rice ( Oryza sativa ). We show that Myc-LCOs and tetra-acetyl chitotetraose (CO4 ) activate the common symbiosis signaling pathway, with resultant calcium oscillations in root epidermal cells of Medicago truncatula and Lotus japonicus. The nature of the calcium oscillations is similar for LCOs produced by rhizobial bacteria and by mycorrhizal fungi; however, Myc-LCOs activate distinct gene expression. Calcium oscillations were activated in rice atrichoblasts by CO4, but not the Myc-LCOs, whereas a mix of CO4 and Myc-LCOs activated calcium oscillations in rice trichoblasts. In contrast, stimulation of lateral root emergence occurred following treatment with Myc-LCOs, but not CO4, in M. truncatula, whereas both Myc-LCOs and CO4 were active in rice. Our work indicates that legumes and non-legumes differ in their perception of Myc-LCO and CO signals, suggesting that different plant species respond to different components in the mix of signals produced by arbuscular mycorrhizal fungi.